(untitled) (Journal of Plant Disease Sciences, 2025)
Downy mildew, caused by Pseudoperonospora cubensis, is a major limiting factor in cucumber production, especially during the Kharif season under humid conditions. The present study was carried out to assess the field resistance of twelve cucumber cultivars against downy mildew during the Kharif 2023 season. Observations were made on the time of first disease appearance and percent disease index (PDI) at different crop stages. The disease first appeared between 34 to 47 days after sowing (DAS), with Lalit-22 showing the earliest and Pant Khira-1 the latest onset. At 40 DAS, nine cultivars showed no symptoms, while Lalit-22, Honey, and Netra-007 showed early infections with PDIs of 15.66%, 12.06%, and 14.33%, respectively. By 70 DAS, disease severity had progressed in all cultivars, with final PDI values ranging from 23.85% to 71.66%. Based on disease response, Ankur-07 and Gujarati Nirmala-2 were rated as moderately resistant, whereas Lalit-22, Honey, and Netra-007 were found susceptible. The remaining cultivars were moderately susceptible. The findings underscore the importance of delayed disease onset and reduced final severity as indicators of resistance. Cultivars Ankur-07 and Gujarati Nirmala-2 may be valuable genetic resources for breeding programs aimed at improving downy mildew resistance in cucumber.